Causal Loop Analysis and Improvement Areas of AS 9100 Aerospace Quality Management System Implementation in Turkish Aerospace and Defence Industry Supply Chain - MuhteÅŸem GÃ¶khan YÃ¼cel; Berk Ayvaz (International Journal of Supply Chain Management, 2019)
Abstract Implementing Aerospace Quality Management system in an organization in theory will achieve on-time delivery, product conformity and acceptable price, which will result in Customer Satisfaction. However, system dynamics has to be considered for all systems, which determines and analyses feedback effects of components in the system. This study investigates these dynamic effects arising from various aspects that organizations are facing during implementation of the aerospace quality management system in Turkish defence and aerospace industry. Results achieved, and information collected through site activity is used to develop causal loop diagram. Requirements of the AS 9100 standard are interpreted to propose improvement opportunities. Causal Loop diagram is validated by using a scientific method.